2019
DOI: 10.7126/cumudj.553220
|View full text |Cite
|
Sign up to set email alerts
|

Lower Incisor Inclination in Relation to Head Posture, Tongue and Hyoid Positions

Abstract: Objectives: To investigate the relationship between head posture, hyoid bone, tongue position and lower incisor inclination. Materials and Methods: The study sample consisted of 98 subjects (35 males, 63 females), who had a mean age of 17.7 years in the permanent dentition and with a skeletal Class I relationship. Lower incisor inclination, craniovertical, craniocervical and craniohorizontal postural variables, tongue and hyoid position and airway measurements were evaluated on lateral cephalograms taken in na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Given the results of studies by foreign authors from around the world [9,14,20,24], which identified and proved the existence of links between cephalometric indicators and odontometric indicators for the local population, and more, the detection of sexual dimorphism, it is appropriate application of anthropology in order to identify the relationship between the size of the cerebral and facial skull and certain indicators of the dental and maxillofacial apparatus for the population of Ukraine, taking into account their regional affiliation and gender.…”
Section: Introductionmentioning
confidence: 99%
“…Given the results of studies by foreign authors from around the world [9,14,20,24], which identified and proved the existence of links between cephalometric indicators and odontometric indicators for the local population, and more, the detection of sexual dimorphism, it is appropriate application of anthropology in order to identify the relationship between the size of the cerebral and facial skull and certain indicators of the dental and maxillofacial apparatus for the population of Ukraine, taking into account their regional affiliation and gender.…”
Section: Introductionmentioning
confidence: 99%